2011
DOI: 10.1179/2047773211y.0000000007
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected results from large-scale cryptosporidiosis screening study in calves in Tanzania

Abstract: A study was undertaken to investigate Cryptosporidium infection in crossbreed dairy calves in two districts in Tanzania. A total of 943 fecal samples from 601 dairy calves were included in the study, with calves from both smallholder dairy farms and from large-scale and medium-scale dairy farms. The modified Ziehl-Neelsen (mZN) technique was used to examine 710 samples, and 13 of these were considered to be positive for Cryptosporidium. These 13 samples considered positive by mZN, along with the remaining 233 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Another potential factor of importance for the lack of infection with C. parvum in African cattle is cattle breed (and, correspondingly, could also be relevant for small ruminant livestock). As noted by Chang'a et al (47), most studies on Cryptosporidium in cattle involve Bos taurus breeds, but B. indicus breeds (which often predominate in African farms) may (145) also supports the suggestion that particular breeds may be more susceptible to Cryptosporidium infection, with significantly higher prevalences of infection reported from Mafriwal cattle (Sahiwal × Friesian crosses) and from Jersey × Friesian crosses. In Africa, a study from Zambia (70) considered that the significantly higher prevalence of Cryptosporidium infection in dairy-farm cattle compared with beef calves or "traditionally reared" calves was due to the management factors.…”
Section: Summary Of Why Zoonotic Transmission May Be Expected In Africamentioning
confidence: 71%
See 2 more Smart Citations
“…Another potential factor of importance for the lack of infection with C. parvum in African cattle is cattle breed (and, correspondingly, could also be relevant for small ruminant livestock). As noted by Chang'a et al (47), most studies on Cryptosporidium in cattle involve Bos taurus breeds, but B. indicus breeds (which often predominate in African farms) may (145) also supports the suggestion that particular breeds may be more susceptible to Cryptosporidium infection, with significantly higher prevalences of infection reported from Mafriwal cattle (Sahiwal × Friesian crosses) and from Jersey × Friesian crosses. In Africa, a study from Zambia (70) considered that the significantly higher prevalence of Cryptosporidium infection in dairy-farm cattle compared with beef calves or "traditionally reared" calves was due to the management factors.…”
Section: Summary Of Why Zoonotic Transmission May Be Expected In Africamentioning
confidence: 71%
“…Many of these studies use modified Ziehl-Neelsen (mZn) for identification; this has low sensitivity and specificity, and does not enable identification of the Cryptosporidium species. Studies using more accurate tests have revealed contrasting results; for example, a study from Tanzania used, in addition to mZn, immunofluorescent antibody testing (IFAT), auramine phenol staining, and molecular methods to investigate calves for Cryptosporidium infection and, using the latter methods, did not detect Cryptosporidium shedding in 943 calf samples, of which over 6% were diarrheic, despite some positive results with mZn (47). The authors suggest that data obtained using mZn should be treated with caution.…”
Section: Veterinary Health Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this latter study also reports the presence of ‘ Cryptosporidium ‐like particles’ – suggesting that objects with epitopes that cross‐react with the anti‐ Cryptosporidium monoclonal antibody used in DFA may be excreted in low numbers in the faeces of non‐human primates. It might be speculated that in some studies that report high Cryptosporidium prevalence, a misidentification may have occurred; this would not be a unique situation, as such misidentification has previously been proposed regarding Cryptosporidium excretion in cattle in sub‐Saharan Africa . Alternatively, these might indeed by Cryptosporidium oocysts, but the numbers are insufficient for successful molecular confirmation.…”
Section: Discussionmentioning
confidence: 95%
“…Bovine faecal samples cattle [63][64][65][66][67]. In all these studies young stock were more affected than adults.…”
Section: Protozoan Species Other Than Eimeriamentioning
confidence: 99%